2009
DOI: 10.1093/intimm/dxp097
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of IFN-γ in CFA-mediated protection of NOD mice from diabetes development

Abstract: IFN-gamma signaling-deficient non-obese diabetic (NOD) mice develop diabetes with similar kinetics to those of wild-type NOD mice. However, the immunization of IFN-gamma signaling-deficient NOD mice with CFA failed to induce long-term protection, whereas wild-type NOD mice receiving CFA remained diabetes-free. CFA also failed to protect IFN-gamma receptor-deficient (IFN-gammaR(-/-)) NOD mice from the autoimmune rejection of transplanted islets, as it does in diabetic NOD mice, and from disease transfer by sple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…This hypothesis is further supported by the failure to induce protection with Freund's Complete Adjuvant (CFA) in IFN-g signaling-deficient NOD mice. 32 That study indicated that IFN-g signaling control the susceptibility of pathogenic T cells to the inhibitory activity of Figure 1. Diabetes onset age correlates with Treg, tolerogenic and activated DCs, and IFNg producing (T) cells.…”
Section: Discussionmentioning
confidence: 97%
“…This hypothesis is further supported by the failure to induce protection with Freund's Complete Adjuvant (CFA) in IFN-g signaling-deficient NOD mice. 32 That study indicated that IFN-g signaling control the susceptibility of pathogenic T cells to the inhibitory activity of Figure 1. Diabetes onset age correlates with Treg, tolerogenic and activated DCs, and IFNg producing (T) cells.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, immunisation with complete Freund's adjuvant (CFA) increases T cell numbers and protects NOD mice from diabetes [29,33]. Mori et al have reported that IFN-γR deficiency abrogates cyclophosphamide-induced acceleration of diabetes and CFA-mediated protection in NOD mice [34,35]. Thus, Th17 cell development and IFN-γ signalling may play a critical role in diabetes susceptibility mediated by lymphopenia-induced homeostatic expansion in NOD mice, although the precise kinetics and mechanisms of severe lymphopenia in these mice are still being elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our in vivo competitive assay also suggests that IFN␥R Ϫ/Ϫ T cells are equally capable of differentiating into Th1 cells (and Th2 and Th17 cells as well; supplemental Figure 10), which is in agreement with the previous reports that IFN␥R Ϫ/Ϫ T cells can normally differentiate into IFN␥-producing Th1 cells and IL-17 ϩ Th17 cells. 38,39 Because the ratio of Tregs to non-Tregs is inversely correlated with GVHD severity, 20 we also measured the ratio of donor T cell-derived CD4 ϩ FOXP3 ϩ Tregs to CD4 ϩ FOXP3 Ϫ T cells in the peripheral blood from mice transplanted with either WT or IFN␥R Ϫ/Ϫ Tconvs on day 30 after allo-HSCT and found no statistical difference between the groups (P ϭ .1063, n ϭ 5). Alternatively, it is also possible the IFN␥R Ϫ/Ϫ Tconvs secrete more Treg-specific chemokines/chemo attractants.…”
Section: Org Frommentioning
confidence: 99%